Internalized stigma among patients with depression: Comparison between employed and unemployed group / Naemah Abdul Rahim - Naemah, Abdul Rahim (2016)
Internalized stigma among patients with depression: comparison between employed and unemployed group. Introduction Experiences of depression are often accompanied by perceptions of stigma. Internalized stigma has a variety of adverse effects such as lower self- esteem, impaired social adaptation, unemployment, reduced adherence to psychiatric medication and limited social support. Identifying potential risk that can become barrier to recovery will help in managing people with depression. Objectives General objective of this study was to assess internalized stigma among patients with depression. The secondary objective for this study was to identify the possible factors that might be associated with internalized stigma among people diagnosed with depression. Method This was a cross-sectional study. The study done on patients who had been diagnosed to have depression for at least a month, who attending outpatient psychiatric clinic in Hospital Raja Permaisuri Bainun Ipoh. Ethical approval had been obtained from Ethic committee Ministry of Health. The participants were given socio-demographic questionnaire and ISMI scale to be answered. The participants then were assess for severity of depression based on Hamilton Depression Rating Scale (HAM-D). Medical records were traced to fill in the clinical history. Statistical analysis was done using v Statistical package for Social Science (SPSS) version 22.0 software. Univariate and multivariate analysis was done for the associated factors. Results 204 patients were recruited among depressed patients. 70% of the patients were having internalized stigma, ranging from mild to severe in severity. After univariate analysis, severity of depression (p < 0.001) and past history of suicide (p=0.037) was found to have significant positive association with high levels of internalized stigma among people with depression. Only severity of depression was found to be significant after multivariate analysis done. No association was seen between levels of internalized stigma with employment status and other demographic profile. Conclusion This study found significant association between levels of internalized stigma with severity of depression and past history of suicide in patients who had depression. This positive correlation could indicate that screening for internalized stigma among people with depression may help in improving management of people with depression, in term of improving severity of depression and suicide prevention.